Cidades pulsantes : dimensões de potencialidade para o turismo urbano - Osmainschi, Ramon (My University, 2018)
More than half the world's population lives in urban centers. And, gradually, the demand, by parts of these residents, for attractions, entertainments and experiences, of the urban scene, that condition moments of recreation and vacancy, increases. Cities are talents and knowledge makers since the dawn of civilization, and contemplate a range of services and facilities that are shared between their inhabitants and temporary users, both consumers of the place and their urbanity. This research seeks, through an infometric survey, to present the global cities that stand out in the current scenario and, through a categorization of global indices, to consolidate analysis dimensions to potentiate urban centers by compiling case studies on the these approaches.As contributions of the research, it is understood that there are possibilities to qualify the city and, respectively, its users, through alternatives that can base later studies. Therefore, in this context, urban tourism stands out with its diversity of events and possibility of going through varied experiences and cultures, without suffering from the seasonality of other examples of tourism activity, and in this modality global cities have a fundamental role. In addition to its economic power, its worldwide reputation through tourism and the quality of life of its residents attract the attention of tourists and inspire the urban planning strategies of other cities on the planet.
Mais da metade da população mundial reside em centros urbanos. E, progressivamente aumenta a procura, por partes destes residentes, por atrativos, entretenimentos e experiências, da cena urbana, que condicionem momentos de recreação e vacância. As cidades são formadoras de talentos e de conhecimento desde os primórdios das civilizações, e contemplam uma gama de serviços e de facilidades que são compartilhados entre seus habitantes e usuários temporários, ambos consumidores do lugar e de sua urbanidade. Esta pesquisa busca, através de um levantamento infométrico, apresentar quais são as cidades globais que se destacam no cenário atual e, através de uma categorização de índices mundiais, consolidar dimensões de análise para potencializar centros urbanos, através da compilação de estudos de caso sobre a aplicação destas abordagens. Como contribuições da pesquisa, entende-se que existem possibilidades de qualificar a cidade e, respectivamente, seus usuários, por meio de alternativas que possam embasar estudos posteriores. Portanto, neste contexto, o turismo urbano destaca-se com sua diversidade de eventos e possibilidade de transcorrer por vivências e culturas variadas, sem sofrer com a sazonalidade de outros exemplos de atividade turística, e nesta modalidade as cidades globais têm um papel fundamental. Além de seu poder econômico, sua reputação mundial através do turismo e da qualidade de vida de seus moradores atraem as atenções de turistas e inspiram as estratégias de planejamento urbano das demais cidades do planeta
Keywords: Turismo e planejamento urbano; Tourism and city planning